Convenient Synthesis of 3-Vinyl and - Gordo, Joana (2011)
A variety of 2-hydroxy aldehydes on reaction with 3-butenoic acid afford in a one-pot reaction the corresponding 3-vinylcoumarins. As expected, extension of the delocalized π-electron system accomplished by Heck coupling reactions with aryl halides results in an increased fluorescence of the compounds whose applicability is yet to be established.